Critical appraisal of ceftaroline in the management of community-acquired bacterial pneumonia and skin infections - Goodman JJ; Martin SI (Dove Medical Press, 2012)
Julian J Goodman, Stanley I MartinDivision of Infectious Diseases, The Ohio State University, Columbus, OH, USAAbstract: Ceftaroline is a novel broad-spectrum cephalosporin ß-lactam antibiotic with activity against methicillin-resistant Staphylococcus aureus (MRSA) as well as multidrug-resistant Streptococcus pneumoniae among other routine Gram positive and Gram negative organisms. It has been approved by the US Food and Drug Administration for treatment of community-acquired bacterial pneumonia and acute bacterial skin and skin structure infections (ABSSSIs). Ceftaroline is approved for treatment of ABSSSI due to MRSA, however currently there are no data for pneumonia due to MRSA in humans. Herein we review the major clinical trials as well as ceftaroline microbiology, pharmacokinetics, and safety, followed by a look at further directions for investigation of this new agent.Keywords: ceftaroline, pneumonia, skin infection